2013
DOI: 10.1080/15235882.2013.818075
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual Two-Way Immersion Programs Benefit Academic Achievement

Abstract: The effects of bilingual education on reading and math achievement were examined by comparing test scores across different elementary-school programs. Results revealed that bilingual Two-Way Immersion programs benefited both minority-language and majority-language students. Minority-language students in Two-Way Immersion outperformed their peers in Transitional Programs of Instruction, while majority-language students in Two-Way Immersion outperformed their peers in Mainstream monolingual classrooms. Bilingual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(64 citation statements)
references
References 42 publications
3
57
0
4
Order By: Relevance
“…Both Spanish-dominant and English-dominant TWI students outperformed their peers in reading and language comprehension in English (Thomas & Collier, 2002). One representative study found that TWI students outperformed their peers in math and science as well (Marian, Shook, & Schroeder, 2013). Other studies have revealed similar results (Alanís, 2000;Senesac, 2002;Lindholm-Leary, 2012).…”
Section: Successes Of Two-way Immersionsupporting
confidence: 64%
“…Both Spanish-dominant and English-dominant TWI students outperformed their peers in reading and language comprehension in English (Thomas & Collier, 2002). One representative study found that TWI students outperformed their peers in math and science as well (Marian, Shook, & Schroeder, 2013). Other studies have revealed similar results (Alanís, 2000;Senesac, 2002;Lindholm-Leary, 2012).…”
Section: Successes Of Two-way Immersionsupporting
confidence: 64%
“…Much of this research has focused on children in low SES environments, but Marian, Shook, and Schroeder (2013) extended the question to investigate whether these results would be similar for Spanish-speaking low SES children and monolingual English-speaking middle-class children who were in Spanish-English bilingual programs and were instructed through Spanish from kindergarten. The numbers of children in each of the relevant groups defined by language and social background, grade, and education program were vastly different (ranging from 6 to 624), so non-parametric analyses were used and results need to be interpreted cautiously.…”
Section: Other Academic and Cognitive Achievementsmentioning
confidence: 99%
“…When a teacher observes a student struggling in class, his or her response will depend on that teacher's own capacity and on the resources available in the school. If initial adjustments to the 41 For effects of two-way bilingual education, see for example, Marian et al ( 2013 ). 42 For a defi nition and description of RTI, see the RTI Action Network website, http://www.rtinetwork.org/learn/what/whatisrti 43 One approach to developing a truly inclusive fi rst-tier instructional approach is to follow the principles of Universal Design for Learning (UDL) .…”
Section: Implementing a Tiered Approach To Interventionmentioning
confidence: 99%